(untitled) (European Journal of Health Research, 2019)
The use of new technologies in free time is increasingly common among the adolescent population. This habit can have as a consequence a decrease in daily physical activity, thus generating health problems such as overweight and obesity. This research aims to study the daily hours of screen during the free time of 1.264 students of 1st and 4th Secondary Education and check if these are related to the physical activity they practice; In addition, it is proposed to know if there are significant differences in the daily screen hours according to the sex and the school year of the respondents. The results show that 47.7% of the adolescents surveyed spend 5 hours or more a day before the screen, be it television, videogames or using the computer; and in addition, it is a habit more frequent in the students of 4th of ESO. No significant differences were found according to sex, however, there are some according to the school year, more students in the 4th year of ESO than the students in the 1st year of ESO. On the other hand, the lack of relationship between screen hours and the practice of physical activity confirms what was found in other international studies: both activities are compatible because they would occur at different times of the day.